A multi-mode adaptive pushover analysis procedure for estimating the seismic demands of RC moment-resisting frames. (15th June 2020) - Jalilkhani, Maysam; Ghasemi, Seyed Hooman; Danesh, Masood
Highlights: Most of pushover methods are used for estimating the seismic demands of buildings. Multi-mode Adaptive Displacement-based Pushover (MADP) analysis procedure is proposed. MADP is developed for estimating the seismic demands of RC moment-resisting frames. Case study of RC frames under different ground motion intensities is conducted. Results of MADP are in good agreement with those of nonlinear response history analysis. Abstract: The main contribution of this paper is to develop a new multi-mode adaptive pushover analysis procedure for estimating the seismic demands of RC moment-resisting frames. The proposed procedure enhances the seismic demands of conventional pushover analysis methods by combining the advantages of 'multi-modal' and 'adaptive' pushover procedures. The presented method, which has been named the multi-mode adaptive displacement-based pushover (MADP) analysis procedure, estimates the seismic demands of buildings by using several multi-stage modal pushover analyses. Each multi-stage pushover analysis begins with the lateral load pattern proportional to the elastic mode-shape. The pushover analysis is then continued with a new lateral load pattern, constructed based on the story displacements obtained from the previous stage. The lateral force distribution is changed whenever a new plastic hinge is formed in the inelastic structural model. The 'first-mode' inelastic mode-shape of the structure is also used by the MADP method to accurately estimate the value of the target-displacement. The final structural responses are determined by combining the seismic demands obtained by the multi-stage modal pushover analyses using an appropriate modal combination rule. The accuracy and efficiency of the MADP procedure is verified using the analysis of four special RC moment-resisting frames with 4-, 8-, 12-, and 20-stories. The structural responses are estimated for two different seismic hazards (intensities). A comparison is then carried out between the estimates from the MADP method with those given by the exact nonlinear response history analysis (RHA). The results from two advanced pushover analysis procedures including the modal pushover analysis (MPA) and consecutive modal pushover (CMP) methods are also presented for the purpose of comparison. The results show that the MADP method is able to satisfactorily estimate the critical seismic demands such as interstory drift ratio and the plastic rotation of the hinges for the example buildings, and to provide an advanced nonlinear static procedure for the seismic performance assessment of RC moment-resisting frames.